24th May: Pentecost: Acts 2.1-21 - Camroux, Martin (The expository times, 2015)
The article presents a sermon idea for Pentecost which details the meaning of Chapter 2 of the Acts of the Apostles. Topics covered include how the Holy Spirit built bridges of understanding among people of different backgrounds and cultures and how the Holy Spirit inspired the disciples to take up the cause of the Kingdom of God. It also discusses the Shavuot harvest celebration.